Juridical Review Decision No. 149/Pdt.G/Pn.Sby Regarding The Refusal Of The Law For Divorce By The Judge - Michael Franklin J.W. Simatupang; Kevin Jo Timanta Barus; Rizki Rizki; Itok Dwi Kurniawan (Jurnal Mamangan, 2022)
As for objective in study This is For analyze consequence law he decided marriage consequence divorce as well as analyze How judge 's consideration disconnect Case No.149/Pdt. G/2022/PN. Sby. Study This including in study descriptive with type study normative juridical uses method focused analysis on content decision court that has strength law stay . As for who became problem in study This is the reason the judge refused case divorce in a manner general is because applicant / plaintiff No can prove arguments the lawsuit. Divorce is end from something connection as husband wife , fine wife or husband did lawsuit divorce in court. As for reason rejection divorce in the decisions studied namely: (1) No There is witness And tool proof others, (2) Witness only There is two people and No know tree case , As for conclusions reached among other things law he decided marriage consequence divorce about distribution treasure about right foster child And to debt And Defendant No Once change attitude And No can finish problem House ladder as good husband And responsible answer morally and materially.